Influence of Different Weather Parameters and Dates of Sowings on Growth and Yield of Pre-released Rice (Oryza sativa L.) Cultures - Anil, D.; Siddi, Sreedhar; Ramana, M. Venkata; Bhatt, P. Spandana; Sreenivas, G. (International Journal of Bio-resource and Stress Management, 2022)
The field experiment was conducted during kharif season of 2019 at Agricultural Research Station, Kunaram, Telangana state, India, to study the influence of different sowing dates on growth and yield of pre released rice cultures. The experiment was laid out in split plot design with consisting of four sowing dates (June 2nd week, July 1st week, July 3rd week and August 1st week) in main plots and 4 pre released rice cultures (RNR 21278, JGL 28545, KNM 1638 and WGL 962 and 2 check varieties (KNM 118 and RNR 15048). The experimental findings revealed that the higher values of dry matter accumulation and grain yield (6839 kg ha-1) were recorded with the crop sown on July 3rd week. The crop sown on August 1st week gave lowest values on number of tillers m-2, number of panicles m-2 and grain yield (5029 kg ha-1). Among all pre-released rice cultures, the culture JGL 28545 showed the higher grain yield (6734 kg ha-1) which was on par with the cultures KNM 1638 (6526 kg ha-1) and WGL 962 (6514 kg ha-1). Among the treatment combinations, data results concluded that the rice cultures JGL 28545 and KNM 1638 recorded highest grain yield (7850.0 and 7849.0 kg ha-1), when sowing was taken up on June 2nd week and July 3rd week, respectively. The linear correlation analysis with SPSS-model has been found that grain yield showed negative correlation with evaporation (-0.076) and bright sunshine hours (BSSH) (-0.372) at tillering to maturity stage (P6).